The IL‐21‐TET2‐AIM2‐c‐MAF pathway drives the T follicular helper cell response in lupus‐like disease. Issue 3 (28th March 2022) - Wu, Haijing; Deng, Yaxiong; Long, Di; Yang, Ming; Li, Qianwen; Feng, Yu; Chen, Yongjian; Qiu, Hong; Huang, Xin; He, Zhenghao; Hu, Longyuan; Yin, Heng; et al.
Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that involves T follicular helper (TFH ) cell‐mediated humoral immune responses. Absent in melanoma 2 (human AIM2 and murine Aim2) is a well‐known component of the inflammasome in the innate immune system. Surprisingly, we observed that in SLE patients, upregulated levels of AIM2 expression were found in peripheral blood and skin lesions, with the highest levels detected in TFH ‐like cells. In the CD4 cre Aim2 fl/fl conditional knockout mice, a markedly reduced TFH cell response was observed, with significantly lower levels of serum autoantibodies and proteinuria, as well as profoundly reduced renal IgG deposition in pristane‐induced lupus mice. Mechanistically, IL‐21 was found to recruit hydroxymethyltransferase ten‐eleven translocation 2 (TET2) to the AIM 2 promoter, resulting in DNA demethylation and increased transcription of AIM2. In addition, AIM2 could regulate c‐MAF expression to enhance IL‐21 production, which consequently promoted TFH cell differentiation. Our results have identified a role of AIM2 in promoting the TFH cell response and further revealed that the IL‐21‐TET2‐AIM2‐c‐MAF signalling pathway is dysregulated in lupus pathogenesis, which provides a potential therapeutic target for SLE. Abstract : Absent in melanoma 2 (AIM2) is a component of AIM2 inflammasome and links with innate immunity in SLE. Enriched AIM2 level has been found in TFH ‐like cells, in circulated environment and skin lesions in lupus patients. AIM2 affects SLE development by regulating TFH cell differentiation, which is regulated by IL‐21‐mediating TET2 recruitment and interaction between AIM2 and c‐MAF in TFH signalling pathways.